Law Enforcement Barriers to Cross-Border Cybercrime in Indonesia: A Comparative Study with the Philippines - Fadhli Muhaimin Ishaq (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2026)
Cross-border cybercrime poses significant challenges to national law enforcement because digital offenses transcend territorial jurisdictions and rely on volatile electronic evidence. In Indonesia, enforcement remains hindered by fragmented jurisdiction, limited digital forensic capacity, weak mutual legal assistance mechanisms, constrained extradition arrangements, and incomplete harmonization of domestic law with international standards. This article examines these challenges through Lawrence Friedman’s Legal System Theory, focusing on the dimensions of legal structure, legal substance, and legal culture. Employing normative legal research with statute and comparative approaches, the study analyzes primary legal materials, including Law No. 1 of 2024 amending the Electronic Information and Transactions Law, Law No. 27 of 2022 on Personal Data Protection, Law No. 1 of 2023 on the Criminal Code, and the 2001 Budapest Convention on Cybercrime, supported by relevant secondary sources. The findings reveal that Indonesia’s enforcement difficulties arise not only from incomplete legal harmonization but also from weak procedural mechanisms for cross-border electronic evidence, limited institutional capacity, inadequate digital forensic resources, and ineffective international cooperation. A comparison with the Philippines, the only ASEAN member state to have ratified the Budapest Convention, shows that ratification facilitates access to international cooperation and capacity-building programs but does not automatically ensure effective enforcement, as significant implementation gaps remain. The study therefore recommends Indonesia’s conditional ratification of the Budapest Convention through reservation mechanisms that safeguard digital sovereignty, particularly regarding Article 32, accompanied by targeted amendments to the Electronic Information and Transactions Law and the Personal Data Protection Law to strengthen domestic enforcement capacity.